매트리스의 종류가 건강한 성인의 주관적, 객관적 수면의 질에 미치는 영향에 대한 탐색적 연구 - 최재원(Jae-Won Choi), 이유진(Yu Jin Lee), 김수현(Soohyun Kim), 이준기(Joonki Lee), 정도언(Do-Un Jeong) (Sumyŏn--chŏngsin saengni, 2016)
Objectives: We aimed to evaluate the effects of mattress type on both objective and subjective sleep quality in healthy good sleepers. Methods: Fifteen healthy good sleepers with a mean age of 30.8 years participated in this study. A randomized crossover trial was carried out using two different mattress types: a standard mattress and a contour coil mattress. After a night of adaptation, all participants were randomized to either a standard mattress or a contour coil mattress. Then, nocturnal polysomnography was conducted for two consecutive nights. Subjective evaluations were obtained using a self-report questionnaire before and after the polysomnographic recording sessions. Results: The polysomnographic showed no differences in total sleep time, sleep stage, or wake time after sleep onset between the two mattress conditions. Of the polysomnographic variables, only sleep onset latency was significantly reduced for the contour coil mattress. Additionally, participants reported better subjective sleep quality when sleeping on the contour coil mattress, according to the questionnaires. Conclusion: The type of mattress might affect not only subjective, but also objective sleep quality, including sleep onset latency. 목 적 : 일반스프링 매트리스에 비교하여 지지력 등을 향상시킨 컨투어 코일 매트리스가 주관적 및 객관적인 수면의 질을 향상시킬 수 있는지 알아보고자 하였다. 방 법 : 건강하게 수면하는 일반인 대상자 15명을 모집하였다. 연구대상자들은 두 종류의 매트리스에서 잠을 자면서 야간수면다원검사를 시행하였고 검사 전, 후 주관적인 수면의 질에 대한 자가설문지를 작성하게 하였다. 한 연구대상자가 각각 다른 매트리스에서 2일에 걸쳐 야간수면다원검사를 시행하여 얻어진 객관적인 수면변인들과 주관적인 자가 설문지 변수들로 교차설계분석을 시행하였다. 결 과 : 야간수면다원검사에서 측정된 수면잠복기가 컨투어 코일 매트리스에서 잠을 잔 경우 일반스프링 매트리스에서 잠을 잔 경우보다 평균 1.9분 감소하였다. 이외에도 주관적으로 느낀 수면 중 각성횟수, 깊게 잠든 느낌 그리고 잠자리의 편안함이 컨투어 코일 매트리스가 유의하게 더 나은 결과를 보였다. 결 론 : 매트리스가 종류에 따라서 주관적인 수면의 질뿐만 아니라 객관적인 수면의 질에도 영향을 미친다고 할 수 있다.